Factors influencing the capacity of women to voice their concerns about maternal health services in the Muanda and Bolenge Health Zones, Democratic Republic of the Congo: a multi-method study - Eric M. Mafuta; Tjard De Cock Buning; Didier L. Lolobi; Papy M. Mayala; Thérèse N. M. Mambu; Patrick K. Kayembe; Marjolein A. Dieleman (BMC, 2018)
Abstract Background This paper aims to identify factors that influence the capacity of women to voice their concerns regarding maternal health services at the local level. Methods A secondary analysis was conducted of the data from three studies carried out between 2013 and 2015 in the Democratic Republic of the Congo (DRC) in the context of a WOTRO initiative to improve maternal health services through social accountability mechanisms in the DRC. The data processing and analysis focused on data related to factors that influence the capacity of women to voice their concerns and on the characteristics of women that influence their ability to identify, and address specific problems. Data from 21 interviews and 12 focus group discussions (n = 92) were analysed using an inductive content analysis, and those from one household survey (n = 517) were summarized. Results The women living in the rural setting were mostly farmers/fisher-women (39.7%) or worked at odd jobs (20.3%). They had not completed secondary school (94.6%). Around one-fifth was younger than 20 years old (21.9%). The majority of women could describe the health service they received but were not able to describe what they should receive as care. They had insufficient knowledge of the health services before their first visit. They were not able to explain the mandate of the health providers. The information they received concerned the types of healthcare they could receive but not the real content of those services, nor their rights and entitlements. They were unaware of their entitlements and rights. They believed that they were laypersons and therefore unable to judge health providers, but when provided with some tools such as a checklist, they reported some abusive and disrespectful treatments. However, community members asserted that the reported actions were not reprehensible acts but actions to encourage a woman and to make her understand the risk of delivery. Conclusions Factors influencing the capacity of women to voice their concerns in DRC rural settings are mainly associated with insufficient knowledge and socio-cultural context. These findings suggest that initiatives to implement social accountability have to address community capacity-building, health providers' responsiveness and the socio-cultural norms issues.